2003
DOI: 10.1074/jbc.m308026200
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Helical Surfaces of the Transmembrane Segments of Subunits a and c′ of the Yeast V-ATPase Defined by Disulfide-mediated Cross-linking

Abstract: Proton translocation by the vacuolar (H ؉ )-ATPase (or V-ATPase) has been shown by mutagenesis to be dependent upon charged residues present within transmembrane segments of subunit a as well as the three proteolipid subunits (c, c, and c؆). Interaction between R735 in TM7 of subunit a and the glutamic acid residue in the middle of TM4 of subunits c and c or TM2 of subunit c؆ has been proposed to be essential for proton release to the luminal compartment. In order to determine whether the helical face of TM7 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
34
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 81 publications
6
34
0
1
Order By: Relevance
“…Most of the amino acids identified are in the ring-contacting α-helices 7 and 8, except for two highly conserved membrane-embedded aspartate residues: D425 on the short linker connecting α-helices 1 and 2, and D481 on α-helix 3. In addition, cysteine-mediated cross-linking has helped define the location of specific a subunit residues in relation to the c′ subunit (42). These cross-linking results also agree well with the proposed a subunit model (Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Most of the amino acids identified are in the ring-contacting α-helices 7 and 8, except for two highly conserved membrane-embedded aspartate residues: D425 on the short linker connecting α-helices 1 and 2, and D481 on α-helix 3. In addition, cysteine-mediated cross-linking has helped define the location of specific a subunit residues in relation to the c′ subunit (42). These cross-linking results also agree well with the proposed a subunit model (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Other than these differences, comparison of the two states reveals only minor conformational changes in individual subunits, suggesting little flexibility in the enzyme as a whole (Movie S3). The T. thermophilus V/A-ATPase thus seems to be relatively rigid compared with the S. cerevisiae V-ATPase (8) Numerous studies, many by Forgac and coworkers, have investigated the topology, function, and subunit arrangement of the S. cerevisiae V-ATPase V O region (31,34,(38)(39)(40)(41)(42)(43)(44). The model of the a subunit presented here is in excellent agreement with these studies.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Topological studies suggest that the C-terminal domain of subunit a contains nine transmembrane helices (25), with the critical Arg 735 located in TM7 (23). Cross-linking studies have demonstrated that TM7 of subunit a is in close proximity to TM4 of subunit cЈ and TM2 of subunit cЉ (30,31), both of which contain an essential glutamic acid residue (21). Moreover, the data are consistent with swiveling of helices within both subunits a and the proteolipids relative to each other.…”
supporting
confidence: 72%
“…By contrast, His-743 is predicted to be near the lumenal border of TM7 and may therefore contribute to a lumenal hemichannel. The location of Arg-735 within the membrane is supported by the ability to form zero-length cross-links between cysteine residues introduced near Arg-735 in subunit a and cysteine residues near the critical buried glutamic acid residues in TM4 of subunit cЈ or TM3 of subunit cЉ (40,41).…”
Section: Discussionmentioning
confidence: 99%